Giant Cell Arteritis - E. V. Shevchenko; A. M. Izmailova; E. A. Kovaleva; G. R. Ramazanov (Неотложная медицинская помощь, 2025)
Giant cell arteritis is a disease characterized by granulomatous inflammation of large and medium-sized arteries. The aorta and its large branches are most susceptible to pathological changes in this arteritis. The course of giant cell arteritis is often complicated by ischemia in the blood supply basin of the artery involved in the pathological process. Variants of such complications may be ischemic optic neuropathy and retinopathy, limb ischemia, and acute cerebrovascular accident. This review presents current data on the etiology and pathogenesis of giant cell arteritis, prevalence, sensitivity, and specificity of clinical and instrumental signs of this disease, as well as practical recommendations for various treatment methods during exacerbation and remission.